KEPERCAYAAN PADA TAKDIR MASYARAKAT MODERN : (DALAM KAJIAN I’JAZ AL-‘ILMI) - Mhd. Azka Fata Siregar, Desinta Fitriani Simatupang, Muhammad Iqbal Nabawi, Harun Alrasyid (CV. Adiba Aisha Amira, 2024)
The study of belief in destiny (qadar) in modern societies often raises debates between religious belief and rational thought. This article aims to explore the concept of belief in destiny from the perspective of i'jaz al-ilmy (scientific wonder in the Qur'an) and how this view can be harmonized with the lives of modern people who are increasingly affected by the development of science and technology. Using an analytical and descriptive approach, this article examines various views and interpretations related to destiny in the context of the Qur'an and their implications for the thinking and behavior of today's society.